Biomimetic Silica Microspheres in Biosensing - Reema Zeineldin; Gabriel P. Lopez; Sireesha Chemburu; Kyle Fenton (Molecules, 2010)
Lipid vesicles spontaneously fuse and assemble into a lipid bilayer on planar or spherical silica surfaces and other substrates. The supported lipid bilayers (SLBs) maintain characteristics of biological membranes, and are thus considered to be biomembrane mimetic systems that are stable because of the underlying substrate. Examples of their shared characteristics with biomembranes include lateral fluidity, barrier formation to ions and molecules, and their ability to incorporate membrane proteins into them. Biomimetic silica microspheres consisting of SLBs on solid or porous silica microspheres have been utilized for different biosensing applications. The advantages of such biomimetic microspheres for biosensing include their increased surface area to volume ratio which improves the detection limits of analytes, and their amenability for miniaturization, multiplexing and high throughput screening. This review presents examples and formats of using such biomimetic solid or porous silica microspheres in biosensing.